PERBANDINGAN PERJUANGAN PEREMPUAN DALAM NOVEL BANĀT AL-RIYĀDH KARYA RAJĀ - Salbiah, Rahma; Mariyatut Tasnimah, Tatik (Jurnal Studi Agama dan Masyarakat, 2022)
Comparative or comparative research is a study that compares two or more literary works. This study aims to determine the similarities and differences between the literary works being compared. This study focuses on the comparison of the struggles of the main female characters in the novels Nayla by Djenar Maesa Ayu and Banāt Al-Riyādh by Rajā' 'Abd Allāh AṢ-Ṣāni'. The method of analysis used descriptive qualitative method. The results of the study indicate that there are similarities in the struggle of women in obtaining their rights. The difference between the two novels is that Nayla's novel has a dominant female role in fighting for her life both in the domestic and public spheres, while the Banāt Al-Riyādh novel describes a female character who struggles to actualize herself in the confines of patriarchy.